Co-trimoxazole prophylaxis is associated with reduced risk of incident tuberculosis in participants in the Swiss HIV Cohort Study. - Hasse, B; Walker, A; Fehr, J; Furrer, H; Hoffmann, M; Battegay, M; Calmy, A; Fellay, J; Di Benedetto, C; Weber, R; Ledergerber, B (American Society for Microbiology, 2014)
Co-trimoxazole reduces mortality in HIV-infected adults with tuberculosis (TB), and in vitro data suggest potential antimycobacterial activity of co-trimoxazole. We aimed to evaluate whether prophylaxis with co-trimoxazole is associated with a decreased risk of incident TB in Swiss HIV Cohort Study (SHCS) participants. We determined the incidence of TB per 1,000 person-years from January 1992 to December 2012. Rates were analyzed separately in participants with current or no previous antiretroviral treatment (ART) using Poisson regression adjusted for CD4 cell count, sex, region of origin, injection drug use, and age. A total of 13,431 cohort participants contributed 107,549 person-years of follow-up: 182 patients had incident TB-132 (73%) before and 50 (27%) after ART initiation. The multivariable incidence rate ratios for cumulative co-trimoxazole exposure per year for persons with no previous ART and current ART were 0.70 (95% confidence interval [CI], 0.55 to 0.89) and 0.87 (95% CI, 0.74 to 1.0), respectively. Co-trimoxazole may prevent the development of TB among HIV-positive persons, especially among those with no previous ART.